Vagabond : a memoir - Curry, Tim (Grand Central Publishing, 2025)
"A celebration of Tim Curry's life's work -- including the iconic Dr. Frank-N-Further in "The Rocky Horror Picture Show" -- and a testament to his profound impact on the entertainment industry as we know it today, There are few stars in Hollywood today that can boast the kind of resume Emmy award-winning actor Tim Curry has built over the past five decades. From his breakout role as Dr. Frank-N-Furter in "The Rocky Horror Picture Show" to his iconic depiction as the sadistic clown Pennywise in It to his critically acclaimed role as the original King Arthur in both the Broadway and West End versions of Spamalot, Curry redefined what it meant to be a "character actor," potraying heroes and villains alike with complexity, nuance, and a genuine understanding of human darkness. He's had dozens of roles across movies, tv shows, and musicals; lent his instantly recognizable voice to dozens of voice roles, audiobooks, and videogames; and he's changed the lives of countless fans in the process. Now, in his memoir, Curry takes readers behind-the-scenes of his rise to fame from his early beginnings as a military BRAT with difficult family dynamics, to his formative years in boarding school and university, to the moment when he hit the stage for the first time. He goes in-depth about what it was like to work on some of the most emblematic works of the 20th century, constantly switching between a camera and a live audience. He also explores the voicework that defined his later career and provided him with a chance to pivot after surviving a catastrophic stroke in 2012 that nearly took his life. With the upcoming 50th anniversary of "The Rocky Horror Picture Show" and the 40th anniversary of Clue, there's never been a better time for Tim to share his story with the world"-- Provided by publisher.